Comparative Analysis of Employee Training Using Conventional Methods and Virtual Reality - David Krákora; Petr Hořejší; Andrea Šimerová (Tehnički Glasnik, 2025)
This paper deals with an innovative method of employee training. Its concept is based on an experiment comparing a conventional training method with virtual reality (VR) training. For the evaluation, a questionnaire was designed to assess how much probands remembered immediately after the training. The area of training was the handling of sharp objects in a healthcare environment. The length of both types of training was 30 minutes). The conventional training was in the form of a presentation, the innovative one was virtual reality with guided interaction with objects. The probands were college students. A total of 42 samples were measured, where each proband was trained on only one variant. The main objective was to compare the effectiveness of each training method as a function of time and its effectiveness in terms of memorability. It showed that probands who acquired knowledge using the VR variant remembered more information. It was also found that prior experience with VR did not yield better results.